Analisis Putusan Pengadilan Tata Usaha Negara (PTUN) Jakarta Nomor 64/G/2018/PTUN.JKT dalam Penegakan Disiplin Profesi Kedokteran: Analysis of The Jakarta State Administrative Court Decision Number 64/G/2018/PTUN.JKT on Enforcement of Medical Professional Discipline - Faradiansyah, Berlian Shinta; Iman, Muhammad Baharul (Jurnal Hukum dan Etika Kesehatan, 2026)
The Jakarta Administrative Court (PTUN) Decision Number 64/G/2018/PTUN.JKT represents a significant milestone in the development of administrative law in Indonesia, particularly in enforcing medical professional discipline. This decision affirms that administrative sanctions imposed by the Indonesian Medical Discipline Honor Council (MKDKI) and the Indonesian Medical Council (KKI), such as the revocation of a Registration Certificate (STR), constitute a State Administrative Decision (KTUN) that may be legally reviewed by the Administrative Court. Using a juridical normative and qualitative approach, this study examines the implications of the decision on transparency, accountability, and legal protection within disciplinary procedures for medical professionals. The findings indicate that this ruling strengthens the principle of legality, enhances access to justice for medical practitioners, and expands the jurisdiction of administrative courts over professional bodies. Furthermore, the decision underscores the need to harmonize professional ethics, positive law, and principles of good governance. In light of the new regulatory framework under Law No. 17 of 2023 on Health, adaptive legal synchronization is required to ensure that judicial oversight operates effectively while maintaining professional independence and ethical standards in the medical field.